Examining the correlation between Altmetric Attention Score and citation count in the gynecologic oncology literature: Does it have an impact? - Chi, Andrew J. (Gynecol Oncol Rep, 2021)
We sought to determine the correlation between Altmetric Attention Score and traditional bibliometrics in the gynecologic oncology literature. We identified the 10 most-cited gynecologic oncology articles from 5 major gynecology journals and 10 major “oncology” journals that publish on gynecologic oncology during 2014, 2016, and 2018. Article citation count and Altmetric Attention Score (AAS), as well as journal impact factor (IF) and date of Twitter account development were recorded. Pearson's correlation coefficient was used to describe the relationship between AAS, tweets, IF, and citation count. While the median citation counts significantly decreased for the top-cited gynecologic oncology articles from 2014 to 2018 (p < 0.001), the corresponding median AAS continuously increased during this period (p = 0.008). For articles published in 2014 and 2018, there was a strong positive relationship between the median citation count and the median AAS (2014: r = 0.92; 2018: r = 0.97), as well as between the IF (r = 0.78 and r = 0.89, respectively); these correlations were moderate to weak in 2016 (r = 0.5 and r = 0.41, respectively). There was a continuously increasing strong positive correlation from 2014 to 2018 between journal IF and median AAS (2014: r = 0.75; 2016: r = 0.82; 2018: r = 0.92). Gynecologic oncology articles published in higher impact journals are associated with increased social media visibility and attention. Our data support the idea that early online attention scores, like the AAS, might be useful for predicting future citation counts for oncology publications in general and gynecologic oncology specifically.